Identification of a Novel Prognostic Lymphangiogenesis-Related Signature Associated with Tumor Immunity for Guiding Therapy in Lung Adenocarcinoma - Juan Peng; Dan Liu; Hong-feng Zhang; Qi-hao Hu; Wen Chen; Juan Zou; Juan Zhang; Hui Li; An-bo Gao; Yu-kun Li (Analytical Cellular Pathology)
Lymphangiogenesis, an integral contributor to lymphatic metastasis, is a significant reason for the poor prognosis of cancer patients. Anti-lymphangiogenesis treatment is a promising novel therapeutic direction, especially for tumors resistant to conventional therapies. We confirmed the ectopic expression of lymphangiogenesis-related genes (LRGs) in lung adenocarcinoma (LUAD) cohorts based on the TCGA database. We constructed a prediction signature with 15 LRG prognostic signatures (F2RL1, LOXL2, MKI67, PTPRM, GPI, POSTN, INHA, LDHA, LINC00857, ITGA2, PECAM1, SOD3, GDF15, SIX1, and FGD5), and the overall survival (OS) was significantly different between the high- and low-risk groups (TCGA-training: p<0.001, TCGA-test: p=0.02, GSE30219: p<0.001, GSE37745: p=0.002, and GSE50081: p=0.002). Moreover, the risk score was also associated with the PIK3CA and BRCA1 pathways. In the nomogram, the prognostic prediction of the risk score was better than that of clinicopathologic parameters in OS, including age, sex, stage, T stage, N stage, and M stage. In summary, we constructed and validated a 15-LRG signature, which may help predict the prognosis of LUAD and offer a possible direction for future research on downstream molecular mechanisms.